IMPLEMENTASI MONITORING DAN EVALUASI (MONEV) BERBASIS TEKNOLOGI DALAM STRUKTUR ORGANISASI GURU DI PONDOK PESANTREN LA TANSA 1 CIPANAS, LEBAK-BANTEN - Anis Zohariah; Ilkham Suherlan; Ade Fathurrahman (STAI Darul Qalam Tangerang, 2026)
This study discusses the use of digital technology in monitoring and evaluation (monev) activities at La Tansa 1 Islamic Boarding School, Cipanas, Lebak, Banten. The purpose of this study is to examine the implementation and effectiveness of technology in conducting monitoring and evaluation. This research uses a qualitative approach with a case study design to gain an in-depth understanding of technology-based monev practices among teachers. The results show that technology-based monev at La Tansa 1 has been implemented in a structured and continuous manner, not just occasionally. The use of technology helps improve the monitoring of teachers’ performance through a more organized system that can be observed in real time. In addition, technology also encourages the improvement of teachers’ digital skills, making them more adaptive, professional, and efficient in carrying out their duties. The integration of data within the monev system also supports leaders in making more accurate decisions based on clear and measurable information. Overall, the implementation of technology-based monev has a positive impact on improving the quality of learning and student development in the boarding school.